DENGUE FEVER WITH ACUTE LIVER DYSFUNCTION: A CASE SERIES STUDY IN A TERTIARY HEALTH CARE CENTRE IN ARUNACHAL PRADESH - Sorang Tashok; Ratan Ram; Kemba Padu; Karto Ete; Duyu Nobing; Tagru Raju (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Dengue is the most common cause of viral hemorrhagic fever, globally. It is endemic in many tropical countries. Dengue fever is one of the most recent emerging diseases in north eastern states of India with a fast-growing burden over the years. Classically, dengue patients present with fever and rash and in severe cases with bleeding and shock. Liver injury is commonly reported in patients with dengue, and various phases of liver dysfunction have been described as secondary to dengue infection. This case series briey describes the clinical prole of dengue fever with acute liver dysfunction from a tertiary care hospital in Arunachal Pradesh (north-eastern state of India)